Comparison of the Effectiveness of Emotionally-Focused Therapy (EFT) and Mindfulness-Based Schema Therapy (MBST) on Emotion Regulation in Women with Borderline Personality Disorder (BPD) - Afsar , Maryam; Hassani , Fariba; Farzad , Valiollah; Golshani , Fatemeh (Applied Family Therapy Journal (AFTJ), 2023)
Aim: This study was conducted to determine the effectiveness of emotionally-focused therapy (EFT) and mindfulness-based schema therapy (MBST) on emotion regulation in women with borderline personality disorder (BPD). Methods: This was a quasi-experimental study with a pretest-posttest design and a control group with a follow-up phase. The statistical population included all women with BPD who were referred to counseling and psychology centers in Tehran in 2021, of which 45 were selected by convenient sampling and randomly assigned to three groups (15 in the EFT group, 15 people in the MBST group, and 15 in the control group). All three groups were first assessed using the Emotion Regulation Questionnaire (ERQ) (Gras et al., 2003). The EFT group then received Susan Johnson (2019) therapy package and the MBST group received Young, Colosco, and Vishar (2003) for ten 90-minute sessions. Data were analyzed using repeated-measures ANOVA. Results: The research results indicated that the cognitive-behavioral therapy and schema therapy groups were effective in improving self-compassion (F=10.70, P=0.018) in men and women with type 2 diabetes. The findings also indicated that cognitive-behavioral therapy and schema therapy groups were effective in improving self-compassion (F=4.54, P=0.018), self-judgment (F=6.25, P=0.005), and projective identification (F=3.45, P=0.043), and the effect was also stable at the follow-up stage. The results of the post hoc test also indicated that there was no difference between scores of cognitive-behavioral and schema therapy groups in self-compassion and self-compassion, self-judgment, and projective identification (p>0.05). Conclusion: Considering the greater effectiveness of EFT than MBST, it can be concluded that EFT can be used as an effective therapy in the treatment of BPD.